Geophysical and GIS model for assessment of groundwater vulnerability in Owa-Kajola marble mining site, Southwestern Nigeria - Ibrahim, Kehinde Olojoku; Ayanlere, Rukayat Tolulope; Aliyu, Umar Faruk; Adejumo, Azeez Adewale; Aweda, Abdulwahid Kolawole (Journal of Sustainable Natural Resources, 2026)
Despite the economic impact of mining, its negative effects on the environment require an assessment and urgent solution for environmental restoration. The aim of this study was to determine spatial distribution of groundwater vulnerability in Owa-Kajola marble mining site, Southwestern Nigeria using geophysical and GIS model. Vertical electrical sounding (VES) using Schlumberger arrangement was carried out in ten (10) locations. Five (5) geoelectric layers are recognised which include top soil, clay-sandy, sand-clayey, weathered, and fresh basements. Generated curve distributions are QH, HA and H curve types respectively. The first top layer has resistivity values between 82?m to 987?m, thickness of 0.1m to 1.6m, and depth between 0.1m to 1.6m. The second layer is clay-sandy with values ranges between 84?m to 389?m, thickness of 0.2m to 9.2m, depth between 0.3m to 10.8m. Third geoelectric layer is sand-clayey with values between 18?m to 125?m, thickness of 2m to 6.2m and depth of 2.7m to 9.6m, fourth geoelectric layer is weathered basement with values of 19?m to 1145?m, thickness of 0.5m to 50m and depth of 0.8m to 57.3m while the fifth geoelectric layer is fresh basement with resistivity values ranges between 34?m to 2847?m. Estimated aquifer protective capacity revealed that study area has aquifer protective capacity values between 0.00 and 0.69 with moderate zones (30%), weak zone (10%) and poor zones (60%). The moderate zones have values range from 0.23 to 0.69, covering the northern to eastern parts of the area. The weak zone has value of 0.17 in eastern parts while poor zones dominate the western to southern parts with values between 0.00 to 0.01 respectively, thus indicating that most parts of the area are poorly protected and prone to groundwater contamination. ArcGIS software (version 10.8.2) was used to generate groundwater vulnerability maps.  This study shows that geophysical methods and GIS model are effective tools for groundwater vulnerability assessment. The study recommended continuous monitoring of groundwater and seek for control of mining activities to protect groundwater resources.